S93 Is Bcl-2 important in small cell lung cancer?. (16th November 2010) - Lawson, M H; Rassl, D M; Vowler, S L; Cummings, N M; Howat, W J; Murphy, G; Rintoul, R C
Abstract : Introduction: Bcl-2 is an anti-apoptotic protein that has previously been associated with increased cell survival in Small Cell Lung Cancer (SCLC) in vitro . However, several immunohistochemical studies of Bcl-2 expression and survival using patient samples have produced conflicting results. We aimed to determine if Bcl-2 expression has prognostic relevance in SCLC using a unique dedicated SCLC tissue microarray (TMA). Methods: The TMA was constructed using formal in fixed, paraffin embedded diagnostic biopsy samples (endobronchial biopsies, TBNA, CT-guided needle biopsies) from 203 patients diagnosed at Papworth Hospital (Cambridge, UK) between 1998 and 2005. 189 cases had cores of tissue on the completed TMA. There was some attrition due to the small size of individual biopsies. The TMA was stained for Bcl-2 using a standard antibody (DAKO clone 124) and the slides were scored by two readers for both extent and intensity of tumour cell staining. Data from the TMA were then correlated with clinical data. The results obtained were combined with those of previous studies in a meta-analysis. Results: 140 cases had tumour tissue on the TMA that could be evaluated for Bcl-2 staining. Patients with low intensity staining had better overall survival than those with high intensity staining in a Cox regression analysis (HR 0.55, 95% CI 0.33 to 0.94, p=0.03, n=117). The meta-analysis included 510 deaths in 673 cases and showed no significant effect of Bcl-2 on survival (HR 0.91, 95% CI 0.74 to 1.09). Conclusion: This study equals the largest published study of Bcl-2 expression in SCLC. Our data showed improved survival in SCLC patients with lower Bcl-2 expression, consistent with in vitro data and the rationale behind current on-going trials of Bcl-2 antagonists in SCLC. However, our meta-analysis showed no overall effect and this may be due to differences in staining and scoring methods between the studies.